Evaluation of vitamin D levels in term pregnancy and its obstetric outcome in Indian women - Ciryam, Shilpa S.; M., Munikrishna; D., Dayanand C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vitamin D deficiency is currently a global pandemic affecting all age groups. Vitamin D is considered a fundamental hormone in calcium homeostasis and bone health. Risk of vitamin D deficiency increases during pregnancy due to increased maternal and fetal demands and altered vitamin D metabolism. Recently, maternal vitamin D deficiency has been linked to adverse pregnancy outcomes, including preeclampsia, gestational diabetes, fetal growth restriction and preterm birth. Adequate vitamin D status appears to be relevant to health at all ages, and even in prenatal life. Methods: This is a cross sectional, observational study conducted in the department of obstetrics and gynaecology at R. L. Jalappa Hospital. A total number of 160 subjects were included. 5 ml of venous blood was collected and was centrifuged at 3000 rpm and stored at - 80°C till analysis. Analysis of 25-hydroxy Vitamin D was done using ELISA. Results: Majority of the subjects were vitamin D deficient (81.87%) and 12.5% were vitamin D insufficient and only 5.63% were vitamin D sufficient. The prevalence of vitamin D deficiency was more among primigravidas (85.6%) and was associated with higher rates of caesarean section (92.4%). High prevalence of vitamin D deficiency was seen in lower middle socioeconomic class (62.5%). Maternal vitamin D deficiency was associated low birth weight of neonates (100%). Conclusions: In this study it was concluded that majority of subjects were vitamin D deficient and belonged to lower middle socioeconomic class. Majority of this subjects who underwent caesarean section were vitamin D deficient. Vitamin D deficiency was associated only with low birth weight of neonates and no other adverse obstetric outcome.